Respuesta :
This might help. I was not sure if you meant -
f(x) = (x+1)
x^3-2x^2+x
or
f(x) = (x+1) -2x^2+x
x^3
So here is both
![Ver imagen poppyeb15](https://us-static.z-dn.net/files/d94/9569d58307fcd45a13afd4c44105b74b.jpg)
![Ver imagen poppyeb15](https://us-static.z-dn.net/files/d67/7a36cf5bcad8672d496de1c02ba9e04d.jpg)
Answer:
The answers is C. For f(x)=(x-1)^2/x^3-2x^2+x
Step-by-step explanation:
This might help. I was not sure if you meant -
f(x) = (x+1)
x^3-2x^2+x
or
f(x) = (x+1) -2x^2+x
x^3
So here is both
Answer:
The answers is C. For f(x)=(x-1)^2/x^3-2x^2+x
Step-by-step explanation: